Aptitudinal and Vocational Perspective of Secondary School Graduate Students in Venezuela’s Capital Region: National Experimental University of the Armed Forces’s Aptitudinal-Vocational Diagnostic Test (Case Study) - Boada, Antonio José (2016)
This paper presents the findings of a comparative study which contrasts the assessment of aptitudinal and vocational profiles of secondary school graduate students with national average results; the selected students were taking the induction course at the National Experimental University of the Armed Forces (UNEFA), given in Eastern Miranda (Guarenas-Guatire), Western Miranda (Ocumare del Tuy, Los Teques, and Santa Teresa del Tuy), and Vargas State. For each location, those results are hierarchically presented in the following way: Verbal ability, numeric ability and logic-abstract knowledge. The vocational level, on the other hand, was measured with a psychometric test related to six dimensions or strengths: knowledge, courage, value, humanity, justice, temperance and level-headedness of character of the subjects in study. Thus, once the aptitudinal and vocational profiles assessment of the population, that took the diagnostic test, was consolidated, results were automatically compared with the profile criteria of the careers offered by UNEFA. By means of the percentage variance formula, it was found that the secondary school graduates of Caracas and Vargas showed an aptitudinal-vocational maturity significantly higher than those in Miranda regions and the national average results. This differed from the results obtained by the secondary school graduate students of Miranda regions whose results were lower than in relation to the national average.